Using the Model, Lead, and Test Technique and “GoTalk NOW” App to Teach Children With Intellectual and Developmental Delays to Correctly Request - Almalki, Nabil Sharaf (Frontiers in Psychology, 2022)
Augmentative and alternative communication systems have been successfully used to help pupils with intellectual and developmental disabilities for functional communication skills. While the effects of the GoTalk NOW application (app) available on the iPad have been investigated, no such study has been conducted in Saudi Arabia. This study investigated the effects of the “model, lead, and test” technique paired with the GoTalk NOW app, used to teach four children with intellectual and developmental delays to correctly request. The participants were four children (three males and one female) from 6 to 8 years of age with intellectual and developmental disabilities. A multiple baseline design was implemented across all participants. All four participants made clear progress using the GoTalk NOW app on the iPad, and implementation of the model, lead, and test technique was successful in helping the participants request correctly and independently. The current study provided a practical, effective, and easy-to-use method for special education teachers to teach children with disabilities. It contributes to expanding the range of teaching options for children with intellectual and developmental disabilities.